Profile Students' Thinking Style From Perspective Gender In Learning Activity - Hasanuddin Hasanuddin (Faculty of Psychology, Universitas Medan Area, 2021)
This article aims to describe the results of data analysis on students' thinking styles which were analyzed for differences in terms of gender differences between men and women.This thinking style is viewed from a complete indicator as the main tool in identifying the state of students' thinking styles including legislative, executive and judicial, monarchy, hierarchical, oligarchic and anarchic, global and local, internal and external, liberal and conservative. This research method is a comparative description model to see the differences in students' thinking styles which are distinguished in the study of age differences and gender differences.The respondents of this study were 610 students spread over high school in the city of Medan in 2020. The results of this study can be used for the benefit of the development of educational psychology in the process of developing the quality of learning in schools, both in the development of the cognitive, affective and psychomotor domains.